Implementasi Metode Simulasi Dalam Memahamkan Materi BAB Shalat Pelajaran Fiqih Kelas III MI Miftahul Ulum 03 Jember - Wirda Lailatul Muqtadiroh; zaeni, Abu (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
Education is the main factor to form children who have faith and devotion to Allah and the problems that are being faced in the world of education are weak education, Learning in Madrasah Ibtidai'ah Miftahul Ulum 03 Has obstacles in learning including understanding prayer, in reading some children are still not memorized. Therefore, in order for students to better understand prayer, there needs to be a variety of methods. For example, in learning fiqh bab shalat using the simulation method, this simulation method can help secure prayers because in this simulation method the child is more into practice regarding the behavior carried out as if in the actual situation, so that the child can more easily understand the prayer.